Good women do not inherit land: Politics of land and gender in India - Rao, Nitya (London Routledge, 2018)
Land for the adivasi Santal women in Dumka, Jharkhand stands for security, social position and identity, and in this men have a distinct advantage. The time period covered is from historic times to the present. The role of government administrative bodies, NGOs and political leaders is also emphasized.